Seroepidemiological study of the transmission of the mumps virus in St. Lucia, West Indies. - Cox, M. J. (Cambridge University Press, 1989)
A seroepidemiological study of the prevalence of mumps virus specific antibodies reveals a pattern of endemic persistence on the island of St Lucia in the West Indies. In the unvaccinated population the proportion seropositive rose rapidly in the child age classes to attain a stable plateau close to unity in value in the teenage and adult age groups. The average age at infection was estimated to be between 3 and 4 years of age and the average duration of detectable levels of maternally derived antibodies was approximately 3 months. Analyses based on mathematical models of the transmission dynamics of the virus suggest that in excess of 75% of each cohort of 1- to 2-year-old children must be effectively immunized to eliminate mumps virus transmission. A mumps radial haemolysis test, developed for quantitative measurements of antibody, is discussed.